(untitled) (Bioresearch Communications, 2022)
Around the world, beef is consumed as a healthy source of protein, fat, niacin, vitamins B6, B12, iron, zinc, and phosphorus. There is mounting evidence that beef is becoming increasingly contaminated with heavy metals, particularly lead (Pb) and chromium (Cr). The purpose of this study was to determine the amounts of the lead (Pb) and chromium (Cr) in beef. Five large markets in Dhaka city—Mirpur-1, New Market, Karwan Bazar, Kaptan Bazar, and town hall market of Mohammadpur—were chosen to gather samples of beef. In this study, the Pb and Cr content in beef was estimated by the Zeeman method using graphite furnace atomic absorption spectrophotometer (GFAAS). The microwave digester finished the digestion of beef. The Pb and Cr content in beef were estimated in mg/kg. Total lead (Pb) content in a beef sample of Mirpur -1, New Market, Karwan Bazar, Kaptan Bazar and Mohammadpur was found to be 0.563±0.084, 0.845±0.127, 0.159±0.024, 0.063±0.009 and 0.143±0.021 mg/kg respectively (Minimum detection limit is 0.06 mg/kg). On the other hand, total chromium (Cr) content in beef sample from Mirpur -1 was found below the detection limit of the method (Minimum detection limit is 0.05 mg/kg). The Cr content in beef from New market, Karwan Bazar, Kaptan bazaar and Mohammadpur was found to be 0.05±0.007, 0.052±0.008, 0.121±0.018 and 0.053±0.008 mg/kg respectively. According to Codex Alimentarium Commission (CAC), the acceptable limit of lead content in beef is 0.1 mg/kg and there is no standard for chromium set by international organization like WHO/FAO, CAC. Brazil has set 0.1 mg/kg as permissible chromium content in beef (Ihedioha et al., 2014). Except for Kaptan Bazar, the chromium content was found to be within Brazil’s permissible limit. Surprisingly, only Kaptan Bazar had acceptable lead content that was within the CAC limit. Bioresearch Commu. 9(1): 1196-1202, 2023 (January)